STILL TOO HOT: AN EXAMINATION OF OBSERVED WATER TEMPERATURE, WATER HEATERS CHARACTERISTICS AND SELF- REPORTED TESTING BEHAVIOUR IN A SAMPLE OF URBAN HOMES. (7th October 2012) - Shields, W; Perry, E; McDonald, E; Zhu, J; Gielen, A
Abstract : Background: Tap water burns result in an estimated 1500 hospital admissions and 50 deaths in the USA annually despite national efforts to preset water heaters at the factory. Aims/Objectives/Purpose: This study reports on observed water temperature, water heater characteristics (age, size, capacity, gauge setting) knowledge and reported testing behaviours in a sample of 1033 urban homes. Methods: Data on knowledge, self-reported testing behaviours, observed water temperature, heater characteristics and demographics were recorded as part of a home observation in a randomised community trial which aimed to improve home safety behaviours. Homes were visited between 6–9 months after a visit from the fire department to check the status of home safety behaviours. Results/Outcomes: Hot water was observed to be above the recommended 120 degrees in 41% of homes. In a univariate analysis, electrical water heaters were statistically significantly more likely to have a safe hot water temperature than gas water heaters. In a multivariate logistic regression, water heaters with fewer gallons per person in the household were more likely to be set above the recommended 120 degrees. Knowledge outcomes varied between items ranging from 59% to 87% correct. A minority (14%) of respondents reported having tested the temperature of their tap water. Significance/Contribution to the Field: Our results suggest hot water temperatures remains at dangerously high in our urban sample despite national efforts to preset water heater to safe temperatures at the factory. This research highlights the needs for the use of passive prevention strategies such as anti-scald devices.